Income mobility of individuals in China and the United States - Niny Khor; John H. Pencavel (Institute for the Study of Labor (IZA), 2006)
Though much has been written about annual income inequality in China, little research has been conducted on longer run measures of income inequality and on income mobility. This paper compares income mobility of urban individuals in China and the United States in the 1990s. The following questions are taken up. To what extent are measures of annual income inequality misleading indicators of long-run income inequality? How much income mobility was there in China in the first half of the 1990s and how did this compare with mobility in other countries? Have real income increases been greater for the poor or the rich? How important is the variation in permanent incomes in China and how has this changed?
Keywords: D31; D63; O15; 330; income inequality; income mobility; China; United States; Einkommensverteilung; Soziale Mobilität; China; USA